2020
DOI: 10.1083/jcb.201906021
|View full text |Cite
|
Sign up to set email alerts
|

The Pex3–Inp1 complex tethers yeast peroxisomes to the plasma membrane

Abstract: A subset of peroxisomes is retained at the mother cell cortex by the Pex3–Inp1 complex. We identify Inp1 as the first known plasma membrane–peroxisome (PM-PER) tether by demonstrating that Inp1 meets the predefined criteria that a contact site tether protein must adhere to. We show that Inp1 is present in the correct subcellular location to interact with both the plasma membrane and peroxisomal membrane and has the structural and functional capacity to be a PM-PER tether. Additionally, expression of artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…The peroxisome-ER contact site generated by Inp1 and Pex3 is required to retain peroxisomes in the mother cell. Two recent studies contradicted the "molecular hinge" model as the new model showed that Inp1 is a component of the tether at the peroxisome-plasma membrane contact site (Hulmes et al, 2020;Krikken et al, 2020). The N-terminal 100 amino acids of ScInp1 localizes to the plasma membrane possibly by binding to PI-(4,5)-P2.…”
Section: Peroxisome-plasma Membrane Contact Sitesmentioning
confidence: 95%
See 1 more Smart Citation
“…The peroxisome-ER contact site generated by Inp1 and Pex3 is required to retain peroxisomes in the mother cell. Two recent studies contradicted the "molecular hinge" model as the new model showed that Inp1 is a component of the tether at the peroxisome-plasma membrane contact site (Hulmes et al, 2020;Krikken et al, 2020). The N-terminal 100 amino acids of ScInp1 localizes to the plasma membrane possibly by binding to PI-(4,5)-P2.…”
Section: Peroxisome-plasma Membrane Contact Sitesmentioning
confidence: 95%
“…However, the loss of ScPex30 does not have any effect on the retention of peroxisomes. If the ER plays a role along with Inp1 in peroxisome retention, there might be proteins similar to ScPex30 that are required for the correct positioning of peroxisomes (Hulmes et al, 2020) (Figure 2C). Interestingly, another study also showed that OpInp1 is required for the formation of peroxisome-plasma membrane contact and peroxisome retention.…”
Section: Peroxisome-plasma Membrane Contact Sitesmentioning
confidence: 99%
“…For example, some proteins, such as Pex3, Pex12, Pex27, and Hem14, are not evenly distributed but rather seem to compartmentalize on specific sites of the membrane. While Pex3 was previously shown to compartmentalize on the membrane and form contact sites with the plasma membrane (Hulmes et al, 2020) and the vacuole (Wu et al, 2019), the other proteins were never suggested to have such a distribution. It will be interesting to further study whether this distribution is due to their function in membrane contact sites.…”
Section: High-resolution Imaging Reveals the Sub-organellar Distribution Of The Peroxi-omementioning
confidence: 99%
“…The formation of protein tethers at the mother cell cortex facilitates organelle retention, whereas the association with the actin-dependent myosin V motor Myo2 promotes traffic to the daughter cell of both peroxisomes and mitochondria [ 80 ]. Peroxisomes anchor on the mother cell cortex by forming a tether between Inp1 and peroxisomal Pex3 [ 81 , 82 , 83 , 84 ]. Organelle fission facilitates traffic by the subsequent attachment to Myo2, mediated by Inp2 [ 85 ].…”
Section: Peroxisome and Mitochondrial Dynamics Are Involved In Asementioning
confidence: 99%